Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I only need a hint as to where to go from here. My problem is this:

$$ \dfrac{1+\tan(x)}{\sin(x)}-\sec(x) $$

Here's my work trying to solve the problem, up until I got stuck. Did I make a mistake somewhere or make it more complicated than it should have been?

$$ \dfrac{(1+\tan(x))(\cos(x)}{\sin(x)\cos(x)}-\dfrac{\sin(x)}{\cos(x)\sin(x)}=\dfrac{(1+\tan(x))(\cos(x))-\sin(x)}{\cos(x)\sin(x)}=\dfrac{1+\tan(x)-\sin(x)}{{\sin(x)}}=\dfrac{1}{\sin(x)}+\dfrac{\dfrac{\sin(x)}{\cos(x)}}{\sin(x)}-\dfrac{\sin(x)}{\sin(x)}=\csc(x)+\sec(x)-1 $$

share|cite|improve this question
You neglected $\cos(x)$ in the second line. You didn't multiply $1 + \tan(x)$ by $\cos(x)$ – NasuSama Mar 4 '14 at 3:33
Same technique as your other problems: write everything in terms of $\sin x$ and $\cos x$ (which means you should get rid of $\sec x$ and $\tan x$ and so on). Gather together fractions over a common denominator. Simplify. Use $\sin^x + \cos^2x = 1$. – bubba Mar 4 '14 at 3:48
up vote 2 down vote accepted

The problem is that you neglected $\cos(x)$ after combining the fractional expressions altogether. So from the end of the first line,

$$\begin{aligned} \dfrac{(1 + \tan(x))\cos(x) - \sin(x)}{\sin(x)\cos(x)} &= \dfrac{\cos(x) + \tan(x)\cos(x) - \sin(x)}{\sin(x)\cos(x)}\\ &= \dfrac{\cos(x) + \frac{\sin(x)}{\cos(x)}\cdot \cos(x) - \sin(x)}{\sin(x)\cos(x)}\\ &= \dfrac{\cos(x) + \sin(x) - \sin(x)}{\sin(x)\cos(x)}\\ &= \dfrac{\cos(x)}{\sin(x)\cos(x)}\\ &= \dfrac{1}{\sin(x)}\\ &= \csc(x) \end{aligned}$$

share|cite|improve this answer

Let $ c = \cos(x)$ and $s = \sin(x)$. Then the expression you gave is $$ \frac{1 + s/c}{s} - \frac{1}{c} \\ = \frac{c+s}{cs} - \frac{1}{c} \\ = \frac{c+s}{cs} - \frac{s}{cs} \\ = \frac{c+s-s}{cs} \\ = \frac{c}{cs} \\ = \frac{1}{s} \\ = \csc(x) $$ This same technique will work with all your other similar problems. The only thing you need to know is that $c^2 + s^2 = 1$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.